Real Option Valuation with Stochastic Interest Rate and Stochastic Volatility - Ramdhan Fazrianto Suwarman (Universitas Islam Bandung, 2019)
Abstract. Real options are one of the most interesting research topics in Finance since 1977 Stewart C. Myers from MIT Sloan School of Management published his pioneering article on this subject in the Journal of Financial Economics. Real options are techniques for supporting capital budgeting decisions that adapt techniques developed for financial securities options. The purpose of using this real option is to capture the options contained in projects that cannot be captured by the discounted cash flow model which operates as a basic framework for almost all financial analyzes. The process of valuing real options will be complemented by the stochastic interest rate and stochastic volatility to better capture the flexibility and volatility of the existing economic and financial situation. The valuation will use a Monte Carlo simulation with the MATLAB programming language on crude oil data from the North Sea oil field. Data were obtained from the thesis of Charlie Grafström and Leo Lundquist with the title